Qualitative analysis of negative and positive COVID-19 experiences of frontline client educators in a Canadian maritime province - Devesh Oberoi; Deborah McLeod; Sandra Saraydarian; Janine Giese-Davis (Social Sciences and Humanities Open)
Background: The worldwide COVID-19 pandemic dramatically shifted the ways that citizens lived, increasing rates of mental-health concerns. Frontline-worker stress escalated due to health risks while exposing workplaces ill-equipped to adapt to crises. Educators struggling with occupational stress pre-pandemic were particularly hard hit, as were healthcare and mental-health clinicians and systems. In a Canadian maritime province, we launched a longitudinal proof-of-concept study of a virtual-mental-health intervention to improve quality of life for members of a teachers' union. A vital first question was to understand these frontline educators’ lived experiences during COVID-19 prior to receiving intervention. Method: We selected 60 frontline educators (who were actively working) as study participants from our 9-month rolling consecutive enrollment. At baseline, prior to intervention, they completed an online (Qualtrics) survey including COVID-19 exposures, stressors, and open-ended narrative questions reporting their negative and positive experiences. We reported exposures and stressors and conducted thematic qualitative analysis of their negative and positive experience narratives. Results: During this baseline study (June 2021–March 2022), 24 (of 60) educators reported COVID-19 diagnoses in themselves/friends/family, while 1 educator reported the death of a friend. In a pre-set list of COVID-19 stressors, those most endorsed (77–88%; slight to severe distress) included four issues: 1) inability to see family, 2) and friends, 3) working in a face-to-face environment, and 4) isolation. In qualitative analyses, negative COVID-19 experiences included social isolation, mental/physical health declines, work-life imbalance, loss of major-life-transition events, parenting/caregiver burden, and professional stressors. Positive experiences included slowing down and stepping back, shifting priorities, improved wellbeing, intentional connections, practical benefits, and growth and resiliency. Many reported that COVID-19 had an unforeseen “silver lining” allowing these workers to find solace. Conclusion: General-population cross-sectional and longitudinal papers discuss COVID-19 distress and increasingly report positive experiences. Our study differs by examining frontline educators distressed enough to seek mental-health intervention. We find that themes of distress and resilience provide insight into these workers’ experiences and point to ways institutions could foster resilience.